Simplicial arrangements revisited - Grünbaum, Branko (Ars mathematica contemporanea, 2013)
In connection with the publication of the catalogue B. Grünbaum, A catalogue of simplicial arrangements in the real projective plane, Ars Mathematica Contemporanea 2 (2009), 1-25 of known simplicial arrangements of lines in the real projective plane, and the note B. Grünbaum, Small unstretchable simplicial arrangements of pseudolines, Geombinatorics 18 (2009), 153-160 about small simplicial arrangements of pseudolines, several developments of these topics deserve to be mentioned. The present paper puts these results in perspective, and provides appropriate illustrations.
Keywords: geometrija; geometry; konfiguracije; matematika; mathematics; simplicial arrangement